ANTARA FORMALITAS DAN REALITAS BIMBINGAN PERKAWINAN DALAM MEMBANGUN RUMAH TANGGA BERKUALITAS ANALISIS TEORI SISTEM HUKUM LAWRENCE M. FRIEDMAN DI KUA KECAMATAN WEDI - Anisa Fitri Rohimah; Andi Wicaksono (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Marriage Guidance (Bimwin) is a premarital guidance program designed to equip prospective brides and grooms in building a quality household. This study analyzes the implementation of Bimwin at the Religious Affairs Office (KUA) in Wedi District, Klaten Regency, by examining the gap between the program's objectives and the reality of its implementation. The study used a descriptive qualitative approach through observation, interviews with organizers, facilitators, participants, and alumni of Bimwin, as well as documentation studies. Data analysis was conducted using the Miles and Huberman model within the framework of Lawrence M. Friedman's legal system theory. The results indicate that Bimwin has been implemented, but has not been running optimally due to time constraints, participant work permit constraints, and material compression, so it tends to function as a policy formality. This study enriches the discourse on the effectiveness of family policy by emphasizing that Bimwin's effectiveness is determined by the integration of legal structure, policy substance, and participants' legal culture. The implications of this study indicate the need for reformulation of Bimwin's implementation that is more oriented towards strengthening substantive aspects and internalizing family guidance values.